Noradrenergic modulation of intrinsic and synaptic properties of lumbar motoneurons in the neonatal rat spinal cord - Tartas, Maylis; Morin, France; Barrière, Grégory; Goillandeau, Michel; Lacaille, Jean-Claude; Cazalets, Jean-René; Bertrand, Sandrine S. (Frontiers in Neural Circuits, 2010)
Although it is known that noradrenaline powerfully controls spinal motor networks, few data are available regarding the noradrenergic modulation of intrinsic and synaptic properties of neurons in motor networks. Our work explores the cellular basis of noradrenergic modulation in the rat motor spinal cord. We first show that lumbar motoneurons express the three classes of adrenergic receptors at birth. Using patch-clamp recordings in the newborn rat spinal cord preparation, we characterized the effects of noradrenaline and of specific agonists of the three classes of adrenoreceptors on motoneuron membrane properties. Noradrenaline increases the motoneuron excitability partly via the inhibition of a KIR like current. Methoxamine (α1), clonidine (α2) and isoproterenol (β) differentially modulate the motoneuron membrane potential but also increase motoneuron excitability, these effects being respectively inhibited by the antagonists prazosin (α1), yohimbine (α2) and propranolol (β). We show that the glutamatergic synaptic drive arising from the T13-L2 network is enhanced in motoneurons by noradrenaline, methoxamine and isoproterenol. On the other hand, noradrenaline, isoproterenol and clonidine inhibit both the frequency and amplitude of miniature glutamatergic EPSCs while methoxamine increases their frequency. The T13-L2 synaptic drive is thereby differentially modulated from the other glutamatergic synapses converging onto motoneurons and enhanced by presynaptic α1 and β receptor activation. Our data thus show that the noradrenergic system exerts a powerful and complex neuromodulation of lumbar motor networks in the neonatal rat spinal cord.